TECHNOLOGICAL APPLICATION OF MICROALGAE IN POWER INDUSTRY AND ENVIRONMENTAL PROTECTION - Ilmutdin M. Abdulagatov; Alibek B. Alkhasov; Gasan D. Dogeev; Nariman R. Tumalaev; Rasul M. Aliev; Gasan B. Badavov; Aslan M. Aliev; Asiyat S. Salikhova (Юг России: экология, развитие, 2018)
Abstract. Aim. The aim of the study is to show the possibility and efficiency of large-scale industrial production of microalgae in the Republic of Dagestan for the development of agriculture (feed for animals and poultry) and other technological applications in the food and pharmaceutical industries for the production of algalin flour (eco bread), polyunsaturated fatty acids (omega-3, omega-6) physiologically necessary for humans, biologically active substances (astaxanthin, phycocyanin), new-generation antibiotics, biofuels and other high added value biotechnological products. The problems of using microalgae for bioremediation of the environment, in particular, purification of geothermal waters from phenols before discharging into the sewage system are considered. Methods. Microalgae are grown in closed and open type plants. Valuable algae components can be extracted using supercritical fluid technology of continuous action. Results. We give a comparative evaluation of the efficiency of using microalgae as a biological raw material in comparison with traditionally used oilseeds. Conclusion. For Dagestan, located on the shore of the Caspian Sea, with its warm climate and an abundance of solar and geothermal energy, the development of this technology is a task of great economic importance. The advantages of microalgae technologies are the basis for the creation of large-scale production of microalgae in southern Russia. Biotechnology in Dagestan can become not only profitable, but also a high-tech and innovative industry.